Application Of Core Analysis Data For Formation Evaluation - Herlan Adim (Testing Center for Oil and Gas LEMIGAS, 1998)
The primary goal of most reservoir evaluation studies is the integration of data from various sources to indentify zones with similar fluid flow characteristic, and to define the areal and lateral continuity of such zones. Core data developed on rock samples recovered from a formation or interest zone which a play vital role in exploration programs, well completion and workover operations and in well and reservoir evaluation. Coring is the only mean of obtaining an actual sample of an oil bearing formation to study. These cores, with proper handling and preservation, are used to obtained data which permit accurate evaluation of the oil or gasreservoirs. This paper presents a practical used of core analysis data for formation evaluation of reservoir hydrocarbon and to provide information that will be of practical value to geologists and engineers involved with the interpretation of core analysis data.